2020
DOI: 10.1016/j.scitotenv.2020.139016
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight exposure increased Covid-19 recovery rates: A study in the central pandemic area of Indonesia

Abstract: Covid-19 is a type of influenza virus that surpresses the body's immune system.• Sunlight triggered the vitamin D that increased body immune. • Sunlight correlated significantly toCovid-19 patients recovery in Jakarta, Indonesia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 19 publications
5
99
0
8
Order By: Relevance
“…In Jakarta, Indonesia, hospitals are designed to provide patients sunlight and home patients exercise outdoors (218). In this setting, daily minutes of sunshine were compared with patient recovery, death rates, and incidence (218).…”
Section: Retrospective Chart Reviews Favoring the Hypothesismentioning
confidence: 99%
“…In Jakarta, Indonesia, hospitals are designed to provide patients sunlight and home patients exercise outdoors (218). In this setting, daily minutes of sunshine were compared with patient recovery, death rates, and incidence (218).…”
Section: Retrospective Chart Reviews Favoring the Hypothesismentioning
confidence: 99%
“…8,33,34. Some studies illustrated that sunlight exposure in the morning could stimulate the production of vitamin D that plays a role in absorbing calcium and phosphorous. 35,36 Besides, vitamin D also functions to reduce the overactive immune system, so the amount of white blood cells increases and it can prevent the coronavirus from entering the body. This study showed that a good understanding of infographics did not significantly influence the recommendation of keeping the body's immune system strong during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Geo-environmental conditions have played a substantial role in COVID-19's growth, with some researchers suggesting that countries with warmer climates have demonstrated slower growth (Asyary and Veruswati, 2020;Coccia, 2020;Gupta et al, 2020;Jahangiri et al, 2020;Tomar and Gupta, 2020;Tosepu et al, 2020). Indonesia is different; with the fourth-biggest population in the world, the virus' spread is likely fast due to the dense populations in some regions (Djalante et al, 2020).…”
Section: Covid-19 In Indonesiamentioning
confidence: 99%
“…Therefore, quick and effective actions were required. International experts have expressed concern about Indonesia's ability to overcome the pandemic because the government has not been fully open with its data, and regulations might not have matched the action required to handle the pandemic (Asyary and Veruswati, 2020). Nonetheless, issuing regulations that can enforce pandemic handling can aid in the fight against COVID-19 (Bellizzi et al, 2020).…”
Section: Covid-19 In Indonesiamentioning
confidence: 99%